PFGE characterisation and adhesion ability of Listeria monocytogenes isolates obtained from bovine carcasses and beef processing facilities Author links open overlay panel - Galvão, Newton Nascentes; Chiarini, Eb; Destro, Maria Teresa; Ferreira, Márcia de Aguiar; Nero, Luís Augusto (Meat Science, 2012)
Listeria monocytogenes is a pathogen capable of adhering to many surfaces and forming biofilms, which may explain its persistence in food processing environments. This study aimed to genetically characterise L. monocytogenes isolates obtained from bovine carcasses and beef processing facilities and to evaluate their adhesion abilities. DNA from 29 L. monocytogenes isolates was subjected to enzymatic restriction digestion (AscI and ApaI), and two clusters were identified for serotypes 4b and 1/2a, with similarities of 48% and 68%, respectively. The adhesion ability of the isolates was tested considering: inoculum concentration, culture media, carbohydrate source, NaCl concentration, incubation temperature, and pH. Each isolate was tested at 108 CFU mL− 1 and classified according to its adhesion ability as weak (8 isolates), moderate (17) or strong (4). The isolates showed higher adhesion capability in non-diluted culture media, media at pH 7.0, incubation at 25 °C and 37 °C, and media with NaCl at 5% and 7%. No relevant differences were observed for adhesion ability with respect to the carbohydrate source. The results indicated a wide diversity of PFGE profiles of persistent L. monocytogenes isolates, without relation to their adhesion characteristics. Also, it was observed that stressing conditions did not enhance the adhesion profile of the isolates.
Keywords: Listeria monocytogenes; PFGE; Beef; Adhesion